Turkish Adaptation and Validation of the EMpowerment of PArents in THe Intensive Care (EMPATHIC-30) Questionnaire to Measure Parent Satisfaction in Neonatal Intensive Care Units - Tiryaki, Öznur; Zengin, Hamide; Çınar, Nursan; Umaroǧlu, Mümtaz Mutlu; Latour, Jos M. (Frontiers in Pediatrics, 2020)
Aim: The aim of this study was to translate and validate the shortened version of the “EMpowerment of PArents in THe Intensive Care” (EMPATHIC-30) questionnaire into Turkish to measure parent satisfaction in the Neonatal Intensive Care Units (NICU) Method: The study used a cross-sectional design. The data of the study were collected from parents with infants staying in the NICU of a training and research hospital in Sakarya, Turkey, between July 2018-2019 after obtaining ethical approval. Totally, 238 parents (234 mothers, 4 fathers) agreed to participate in the study and completed the questionnaire. Of these, 35 mothers were recruited one month later for the test-retest reliability analysis. The questionnaire was translated using back and forward translation. Reliability and validity test were performed to measure the psychometric properties of the Turkish EMPATHIC-30. Results: The mean age of the parents was 28.27 (SD 5.93), and 48.3% of them were primary school graduates. The infants: 55.9% were male, the mean gestational age was 36.89 (SD 3.25) weeks, and mean length of hospital stay was 9.36 (SD 10.17) days. The mean scores of each item with a six-point scale of the EMPATHIC-30 questionnaire ranged between 4.01 and 4.87. The Cronbach’s alpha of the total questionnaire was 0.95. Cronbach’s alpha of the five domains (Information, Care and Treatment, Organization, Parent Participation and Professional Attitude) ranged between 0.80 and 0.92. Pearson correlation coefficient between the domains and total questionnaire was r=0.988. The Intraclass correlation coefficient was ICC=0.998 in the test-retest evaluation. Confirmatory factor analysis was performed for construct validity and was moderate; Comparative Fit Index=0.792, Tucker–Lewis Index=0.770, Standardized Root Mean Square Residual= 0.0811, and Root Mean Square Error of Approximation=0.107. Conclusion: The Turkish version of EMPHATIC-30 has adequate psychometric properties. The EMPATHIC-30-Turkish questionnaire is an easy and appropriate instrument which can be used to measure satisfaction of Turkish parents with infants staying in the NICU.